DL-SAFE: Proteção Baseada em Aprendizado Profundo para Detecção de Botnets na Borda - Guimarães, Lucas Chagas de Brito; Couto, Rodrigo de Souza (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2023: Companion Proceedings of the 23rd Brazilian Symposium on Information and Computational Systems Security, 2023)
IoT (Internet of Things) devices are fundamental to multiple sectors, such as smart homes, cities, and grids. However, the existence of billions of devices with limited computing power makes them ideal targets for botnets. This paper proposes DL-SAFE, a tool for real-time traffic classification in edge environments using Open Argus and Pytorch. The tool also allows the evaluation of neural network architectures using 3 types of layers. The results demonstrate the tools’ effectiveness, obtaining precision and recall values greater than 99% for multiple models. With the throughput tests it can be seen that performance varies greatly according to the architecture, with half the evaluated models processing more than 1000 network flows per second.